2019
DOI: 10.1016/j.ebiom.2019.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor 7 promotes the progression of perihilar cholangiocarcinoma by inducing the transcription of c-Myc and FOS-like antigen 1

Abstract: Background: Perihilar cholangiocarcinoma (PHCC) is the most common type of cholangiocarcinoma with the worst prognosis. Radical resection of PHCC is difficult; thus, few effective biomarkers or useful molecular profiles for PHCC have been reported in recent years. Therefore, in this study, we aimed to assess biomarkers for PHCC. Methods: We screened potential biomarkers for PHCC using exome and transcriptome sequencing with PHCC tissues and paired normal tissues. Transcription factor 7 (TCF7) expression was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…The expression of FOS has been proposed to be positively related with the expression of c-Myb in colorectal cancer cells, while the expression of c-Myb is repressed in colorectal cancer tissues, suggesting that expression of FOS is also downregulated in colorectal cancer tissues [ 24 ], which is concordant with the current study. The elevation of FOS-like antigen 1 expression is positively correlated with the progression of perihilar cholangiocarcinoma [ 25 ]. More importantly, a prior research illustrated that FOS was involved in gene expression regulated by TGF-β [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of FOS has been proposed to be positively related with the expression of c-Myb in colorectal cancer cells, while the expression of c-Myb is repressed in colorectal cancer tissues, suggesting that expression of FOS is also downregulated in colorectal cancer tissues [ 24 ], which is concordant with the current study. The elevation of FOS-like antigen 1 expression is positively correlated with the progression of perihilar cholangiocarcinoma [ 25 ]. More importantly, a prior research illustrated that FOS was involved in gene expression regulated by TGF-β [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To detect BST2 protein expression in sample tissues, IHC examination was conducted as described previously. 16 Briefly, deparaffinized and rehydrated slides were treated with 10 mM citrate buffer (pH 6.0) at 95°C for antigen recovery, followed by quenching the endogenous peroxidase activity with 3% H 2 O 2 incubation. 5% Fetal bovine serum (FBS) was then used to block the nonspecific binding sites.…”
Section: Immunohistochemistry (Ihc) and Ihc Analysismentioning
confidence: 99%
“…An important member of the Myc gene family, c-Myc, has been reported that its increased expression was associated with the progression of diverse cancers, including colorectal cancer, prostate cancer, lung cancer, HCC, bladder cancer, and cholangiocarcinoma [46][47][48][49][50][51][52][53][54] . In hepatobiliary cancers, c-Myc mediated small nuclear ribonucleoprotein polypeptides B (SNRPB) upregulation to facilitate the progression of HCC 54 .…”
Section: Discussionmentioning
confidence: 99%